PELATIHAN ASPEK PEMBIAYAAN USAHA UMKM BINAAN KOPERASI BINA CIPTA USAHA DI KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - I Gede Adiputra; Steven Wijaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
This training in community service activities is expected to encourage the pace of steps in advancing economic life in rural areas. This activity aims to provide understanding for MSME actors on the problems they face related to financing aspects in business management. After this activity, participants can understand what is included in the aspect of financing for businesses and the management and control of these financial aspects. The purpose of this study is to improve understanding and awareness of the importance of entrepreneurship, especially creative and innovative financing in order to obtain additional income, as well as improve soft skills, skills in running a business, family living standards based on individual abilities, availability of resources and potential in the community. around, so that later it is hoped that it can be imitated and applied by the village community. The achievement of the objectives of this community service activity is good, this can be seen from the participants' understanding of business management related to risk management and services and the ability of participants to apply risk and provide services as seen from the results of observations during the activity. For sustainability programs, training and assistance related to business management must be held so that the standard of participants is not only limited to the aspect of understanding but also at the level of practice and preparation of business financial reports.